SHADOWING TECHNIQUE TO IMPROVE STUDENT’S LISTENING SKILL - Junipisa, Ni Made Ernila; Aristana, I.N. (Universitas Pendidikan Ganesha, 2021)
The condition that occurs in the classroom is that students are afraid of English. Students feel that learning English is difficult to memorize. Students have learning difficulties because the teacher does not apply a suitable learning model for students. This causes students to feel bored in learning and has an impact on students' low English skills. The purpose of this study is to analyze the shadowing technique in learning English for students. This type of research is classroom action research. The research subjects were 17 students. There are four main parts of classroom action research, namely planning, action, observation, and reflection. The methods used to collect data are observation, interviews, and questionnaires. The technique used to analyze the data is descriptive qualitative and quantitative analysis. The study results are the average value, from 73.2 in the first cycle to 76.0 in the second cycle. The percentage of students who passed the KKM also increased from 59% to 78%. Listening skills improve after the application of shadowing techniques. The key is that the application of shadowing techniques can improve students' listening. This research implies that teachers can apply shadowing techniques in the classroom. The application of shadowing techniques can create a fun learning atmosphere for students to improve students' listening skills.